Konsep Revolusi Mental Presiden Joko Widodo dalam Perspektif Pendidikan Karakter Syed Muhammad Naquib Al-Attas - Sulthon Abdul Aziz; Mohammad Syifa Amin Widigdo (LITERASI (Jurnal Ilmu Pendidikan), 2020)
This research aims to find out the mental revolution concept of president Joko Widodo (known as Jokowi) and the character education concept of Syed Muhammad Naquib Al-Attas and to know the revolution mental of Jokowi viewed from the perspective of character education concept by Syed Muhammad Naquib Al-Attas. This research carried out a document study that focuses on analyzing the literature or documents using qualitative approach and content analysis technique.The findings show that there are significant differences between the mental revolution of Jokowi and character education concept of Syed Muhmmad Naquib Al-Attas referring to 4 pillars of UNESCO namely learn to know, learn to do, learn to live together, and learn to be which are called orderly as cognitive, psychomotor, affective and teleology in this research.Of those 4 aspects, the aspects of teleology and cognitive have major differences. In the cognitive aspect, the mental revolution of Jokowi doesn’t give a large focuses on it. Meanwhile, Syed Muhammad Naquib Al-Attas gives the mainly focuses for this aspect. In the aspect of teleology, the mental revolution by Jokowi aims to create good citizens, while it is to create just people (insan kamil) for Syed Muhammad Naquib Al-Attas.From those two aspects, it is concluded that the mental revolution concept of Jokowi when viewed by the perspective of character education of Syed Muhammad Naquib Al-Attas has been in ta’dib concept in order to be a khalifah. And there are still differences in the aspect of cognitive, that the mental revolution of Jokowi only gives a little focuses on the cognitive aspect.